Correlation analysis of pharmacokinetic parameters of docetaxel AUC and adverse reactions in breast cancer patients - Tang, Yongzhe; Liu, Yamin; Qin, Shengying; Huai, Cong; Zhang, Jin; Ding, Weijie; Fan, Junwei; Wang, Jie; Zhang, Xiaoqing (Frontiers in Pharmacology, 2025)
BackgroundDocetaxel is commonly used in breast cancer chemotherapy. The previous drug dose is generally calculated based on body surface area (BSA). However, the metabolism varies greatly among different patients. Docetaxel therapeutic drug monitoring (TDM) helps monitor adverse drug reactions and explore the appropriate range of area under the curve (AUC) to ensure chemotherapy effectiveness and reduce adverse reaction occurrence.MethodsWe conducted a real-world retrospective study and included 180 breast cancer patients, who received a chemotherapy regimen containing docetaxel. The patients’ demographic and tumor data were reviewed. Adverse reaction data during chemotherapy treatment were collected through patient questionnaires and laboratory test results. Univariate logistic regression analysis was performed on 33 patient indexes, including basic information, blood toxicity, liver and kidney function, gastrointestinal reactions, and cardiotoxicity.ResultsThe adverse reactions of chemotherapy were matched with different docetaxel AUC results through univariate analysis. The patients between the groups were no statistically significant differences in terms of demographic and tumor data, including age, height, weight, BSA, and body mass index (p > 0.05). Univariate analysis revealed significant differences in albumin (ALB) levels (p = 0.037), creatinine (CREA) levels (p = 0.002), nausea occurrence (p = 0.008), vomiting occurrence (p = 0.013), rashes occurrence (p = 0.002), and chemotherapy-induced alopecia incidence (CIA) (p = 0.002). Based on the results of the univariate analysis, binary logistic regression analysis was further conducted to identify predictors contributing to the occurrence of chemotherapy adverse reactions. The results demonstrated that an AUC value greater than 2.5 mg h/L was significantly associated with increased risk of certain adverse reactions such as rashes, CIA, CREA, and ALB.ConclusionThe docetaxel TDM provides a reliable basis for monitoring chemotherapy adverse reactions, with high AUC significantly associated with certain adverse reactions. Future studies are expected to include more patients and conduct multi-center trials to obtain a suitable AUC range for Chinese patients, which will guide the determination of clinical chemotherapy doses and reduce the occurrence of adverse reactions.